Few-nanosecond stripline kickers for top-up injection into PETRA IV. Issue 1 (1st January 2023) - Loisch, G; Belokurov, V; Obier, F
Abstract: PETRA IV is the planned ultralow-emittance upgrade of the PETRA III synchrotron light source at DESY, Hamburg. The current baseline injection scheme is an off-axis, top-up injection with few-nanosecond stripline kickers, which would allow for accumulation and least disturbance of experiments during injection. Besides the requirements on kick-strength, field quality, pulse rise-rate, and heat management, two mechanical designs with different apertures are necessary, as the devices will be used for injection and the transverse multi-bunch feedback system. In this contribution we will present the current status of 3D finite element simulations of electromagnetic fields as well as the mechanical design and first pulse electronics tests.